A Structural View on ESCRT-Mediated Abscission - Horváth, Péter; Müller-Reichert, Thomas (Frontiers in Cell and Developmental Biology, 2020)
The endosomal sorting complex required for transport (ESCRT) mediates cellular processes that are related to membrane remodeling, such as multivesicular body (MVB) formation, viral budding and cytokinesis. Abscission is the final stage of cytokinesis that results in the physical separation of the newly formed two daughter cells. Although abscission has been investigated for decades, there are still fundamental open questions related to the ultrastructure and spatio-temporal organization of the molecular machinery involved in this process. Reviewing knowledge obtained from in vitro as well as in vivo experiments, we give a brief overview on the role of ESCRT components in abscission mainly focussing on mammalian cells.